A Genotypic Analysis of Five P. aeruginosa Strains after Biofilm Infection by Phages Targeting Different Cell Surface Receptors - Pires, Diana P.; Dötsch, Andreas; Anderson, Erin M.; Hao, Youai; Khursigara, Cezar M.; Lam, Joseph S.; Sillankorva, Sanna; Azeredo, Joana (Frontiers in Microbiology, 2017)
Antibiotic resistance constitutes one of the most serious threats to the global public health and urgently requires new and effective solutions. Bacteriophages are bacterial viruses increasingly recognized as being good alternatives to traditional antibiotic therapies. In this study, the efficacy of phages, targeting different cell receptors, against Pseudomonas aeruginosa PAO1 biofilm and planktonic cell cultures was evaluated over the course of 48h. Although significant reductions in the number of viable cells were achieved for both cases, the high level of adaptability of the bacteria in response to the selective pressure caused by phage treatment resulted in the emergence of phage-resistant variants. To further investigate the genetic makeup of phage-resistant variants isolated from biofilm infection experiments, some of these bacteria were selected for phenotypic and genotypic characterization. Whole genome sequencing was performed on five phage-resistant variants and all of them carried mutations affecting the galU gene as well as one of pil genes. The sequencing analysis further revealed that three of the P. aeruginosa PAO1 variants carry large deletions (> 200 kbp) in their genomes. Complementation of the galU mutants with wild-type galU in trans restored LPS expression on the bacterial cell surface of these bacterial strains and rendered the complemented strains to be sensitive to phages. This provides unequivocal evidence that inactivation of galU function was associated with resistance to the phages that uses LPS as primary receptors. Overall, this work demonstrates that P. aeruginosa biofilms can survive phage attack and develop phage-resistant variants exhibiting defective LPS production and loss of type IV pili that are well adapted to the biofilm mode of growth.